2019
DOI: 10.7554/elife.47898
|View full text |Cite
|
Sign up to set email alerts
|

CTCF confers local nucleosome resiliency after DNA replication and during mitosis

Abstract: The access of Transcription Factors (TFs) to their cognate DNA binding motifs requires a precise control over nucleosome positioning. This is especially important following DNA replication and during mitosis, both resulting in profound changes in nucleosome organization over TF binding regions. Using mouse Embryonic Stem (ES) cells, we show that the TF CTCF displaces nucleosomes from its binding site and locally organizes large and phased nucleosomal arrays, not only in interphase steady-state but also immedia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 78 publications
(159 reference statements)
17
108
0
2
Order By: Relevance
“…Secondly, we found that the NRL decrease near CTCF is correlated with CTCF-DNA binding affinity ( Figure 1D and 5F). This result goes significantly beyond previous observations that the CTCF binding strength is related to a more regular nucleosome ordering near its binding site (43,65) and may have direct functional implications.…”
Section: Discussionsupporting
confidence: 43%
“…Secondly, we found that the NRL decrease near CTCF is correlated with CTCF-DNA binding affinity ( Figure 1D and 5F). This result goes significantly beyond previous observations that the CTCF binding strength is related to a more regular nucleosome ordering near its binding site (43,65) and may have direct functional implications.…”
Section: Discussionsupporting
confidence: 43%
“…The architectural protein CTCF insulates adjacent active and repressed chromatin domains and also mediates 3-D contacts at several developmentally regulated genomic loci (Cuddapah et al, 2009;Fu et al, 2008;Narendra et al, 2015;Phillips and Corces, 2009) Owens et al, 2019, Clarkson et al, 2019. In addition to precisely mapping direct transcription factor footprints, CUT&RUN also probes the local and 3-D chromatin environments around CTCF binding sites (Skene and Henikoff, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…5a). Prior reports have described varying degrees of CTCF mitotic retention 20,21,22 . This observation was confirmed by ChIP-qPCR at individual CTCF binding sites (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 95%